Plant population and insect control in upland rice under complementar irrigation - Santos, Alberto Baêta dos; Ferreira, Evane; Aquino, Antonio Renes L. de; Sant'ana, Evaldo Pacheco; Baldt, Alberto Francisco (Pesquisa Agropecuaria Brasileira, 2014)
Field experiments were carried out to study the effect of three row spacing (30 cm, 40 cm and 50 cm), combined with three seed densities (100, 150 and 200 seeds/m2) with and without inseticide application on the seeds (carbofuran) and in sprayer application (monocrotofos) on yield and yield components of rice, in cerrado soil under complementar irrigation. The use of inseticide reduced the attack of insects and increased the number of tiller and panicle/m2, the weight of 100 grains and grain yield. Plant lodging decreased linearly with the increase of row spacing. Without insect control, the row spacing and seed density correlated linearly and positively and independently of grain yield. With insect control there was an interaction between row spacing and seed density, and better grain yield was reached with the treatment of 50 cm between rows and 200 seeds/m2.